2012
DOI: 10.3389/fonc.2012.00110
|View full text |Cite
|
Sign up to set email alerts
|

Development of Coagulation Factor Probes for the Identification of Procoagulant Circulating Tumor Cells

Abstract: Metastatic cancer is associated with a hypercoagulable state, and pathological venous thromboembolic disease is a significant source of morbidity and the second leading cause of death in patients with cancer. Here we aimed to develop a novel labeling strategy to detect and quantify procoagulant circulating tumor cells (CTCs) from patients with metastatic cancer. We hypothesize that the enumeration of procoagulant CTCs may be prognostic for the development of venous thrombosis in patients with cancer. Our appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Therefore, the development of thrombosis may not rely on of the mere initiation of coagulation by circulating TF, but rather the magnitude of the host’s coagulation response to that trigger. Our studies have shown that physiological variance of coagulation factors IX and X influence in vitro coagulation kinetics to equivalent procoagulant TF triggers, and evaluation of individual patient coagulation factor levels may hold promise in predicting who is at greater risk to develop thrombosis in the presence of procoagulant TF or CTCs (117). …”
Section: Clinical Considerations For the Procoagulant Phenotype Ofmentioning
confidence: 99%
“…Therefore, the development of thrombosis may not rely on of the mere initiation of coagulation by circulating TF, but rather the magnitude of the host’s coagulation response to that trigger. Our studies have shown that physiological variance of coagulation factors IX and X influence in vitro coagulation kinetics to equivalent procoagulant TF triggers, and evaluation of individual patient coagulation factor levels may hold promise in predicting who is at greater risk to develop thrombosis in the presence of procoagulant TF or CTCs (117). …”
Section: Clinical Considerations For the Procoagulant Phenotype Ofmentioning
confidence: 99%
“…Thus, by exposing TF and PS on their outer membrane, tumour cells can function as binding surfaces for different proteins of the coagulation cascade (i.e., factors VIIa, VIIIa, IXa, Xa and Va) [25,26] and promote the subsequent assembly of the prothrombinase and tenase complexes, leading to the generation of fibrin in the extravascular environment (Figure 1). TF expression by tumour cells allows for the formation of the extrinsic tenase complex; establishment of the intrinsic tenase and prothrombinase complexes on the surface of various tumour cell lines has also been described, mainly associated with PS exposure [27–31].…”
Section: Extravascular Activation Of Blood Coagulation In Cancermentioning
confidence: 99%
“…Tumors and cancer cell lines have been shown to express the transmembrane glycoprotein tissue factor (TF) (7,28,52). TF is the primary initiator of blood coagulation and is expressed by hematopoietic cells (monocytes) and a variety of nonhematopoietic cells (endothelial cells, epithelial cells, smooth muscle cells, and fibroblasts) (29).…”
Section: Ctc Biochemical Characterizationmentioning
confidence: 99%